Proximal Humerus Reconstruction after Tumor Resection: An Overview of Surgical Management. (20th March 2021) - D'Arienzo, Antonio; Ipponi, Edoardo; Ruinato, Alfio Damiano; De Franco, Silvia; Colangeli, Simone; Andreani, Lorenzo; Capanna, Rodolfo
Abstract : Proximal humerus is one of the anatomical sites that are most frequently involved by bone and soft tissue malignant tumors. Alone or in association with adjuvant treatments, surgery represents the main therapeutic option to treat and eradicate these diseases. Once the first-line option, in the last decades, amputation lost its role as treatment of choice for the large majority of cases in favor of the modern limb sparing surgery that promises to preserve anatomy and—as much as possible—upper limb functionality. Currently, the main approaches used to replace proximal humerus after a wide resection in oncologic surgery can be summarized in biological reconstructions (allografts and autografts), prosthetic reconstructions (anatomic endoprostheses, total reverse shoulder prostheses), and graft-prosthetic composite reconstructions. The purpose of this overview is to present nowadays surgical options for proximal humerus reconstruction in oncological patients, with their respective advantages and disadvantages.